RAGAM POLA TABUHAN TAHAR PADA KESENIAN HADRAH DI DESA LUBUK DAGANG KABUPATEN SAMBAS - Muslim, Agus; Djau, Nurmila Sari; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this study is the curiosity of researchers about the various patterns of tahar wasp in Lubuk Dagang village, Sambas district. The problem in this study is how the various wasps patterns. The method in this research is descriptive method with a qualitative form of research. the approach used is the musicology approach. Data sources in the study are Abdan, Hammam Muhyi and Fadilah. The data in this study are the results of interviews, observations, documentation and notebooks about the various patterns of wasps. Data collection techniques in this study are observation, interview, and documentation techniques. This research data collection tool researchers as the main instrument. Checking the validity of the data uses triangulation and extension of observation. Data analysis techniques in this study are the analysis during data collection and analysis after data collection. The results of this study were six types of wasp patterns namely habban wasps, rabbut wasps, kuttong wasps, bujjor rhythmic beats, bujjor sion wasps and ribbu-ribbu wasps. This study describes each of the various wasp patterns. Each type of wasp pattern has a wasp motif in the form of literal repetition and uses 4/4 measure. Keywords: Various Wasp Patterns, Tahar, Hadrah.